2021
DOI: 10.1007/s12603-021-1611-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty on COVID-19 Outcomes: A Systematic Review and Meta-analysis of 16 Cohort Studies

Abstract: Background: Frail patients are increasingly vulnerable to stress, which is mainly manifested by a reduced physiologic reserve in metabolic and immune systems and neuromuscular system. Several studies found a significant association of frailty with COVID-19 severity to support the evidence for the application of frailty assessment. However, there were contradictory results in other studies. Thus we conducted a systematic review and meta-analysis to synthesize the current studies to investigate impact of frailty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 77 publications
3
42
0
2
Order By: Relevance
“…There have been several other reviews exploring the relationship between frailty and health outcomes for individuals with COVID‐19 75–78 . However, the current review is, to our knowledge, the only living review, most up to date, largest and addresses the widest breadth of outcomes (informed by a widely used health outcome framework, the IHI Triple Aim).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several other reviews exploring the relationship between frailty and health outcomes for individuals with COVID‐19 75–78 . However, the current review is, to our knowledge, the only living review, most up to date, largest and addresses the widest breadth of outcomes (informed by a widely used health outcome framework, the IHI Triple Aim).…”
Section: Discussionmentioning
confidence: 99%
“…There was consolidation, a ground glass appearance, and bilateral involvement on thoracic CT images in 27.7% (36), 35.3% (46), and 36.9% (48) of the patients, re- spectively. The median psoas muscle CSA was 2.09 cm 2 (1.55-3.06), the median PMI was 0.09 cm 2 /kg/ m 2 (0.07-0.12), and the median psoas density was 49.9 (44.6-53.7) on CT images acquired at the time of initial hospital admission. The demographic, clinical, laboratory, and radiological findings of the participants are presented in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have found advanced age, male gender, high Sequential Organ Failure Assessment Scores, and high D-dimer levels and comorbidities to be associated with poor prognosis in COVID-19 patients (3,4). In addition, a recent meta-analysis found that frailty increases the severity, morbidity, and mortality risk associated with COVID-19 (2). Several guidelines, such as the National Institute for Health and Care Excellence guidelines, can be recommended for the assessment of frailty in COV-ID-19 patients over the age of 65 years (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the capable direction of Professor Morley, the journal has striven to gain a better understanding of the clinical implications of the COVID-19 pandemic for older adults. Over 60 Journal's publications, many featuring renowned geriatrics experts, have proposed insightful perspectives and practical solutions to combat the burdens associated with the pandemic, such as social isolation and containment (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%